2017
DOI: 10.1016/j.antiviral.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Solution conformations of a linked construct of the Zika virus NS2B-NS3 protease

Abstract: The Zika virus presents a serious risk for global health. Crystal structures of different constructs of the Zika virus NS2B-NS3 protease (NS2B-NS3pro) have been determined with the aim to provide a basis for rational drug discovery. In these structures, the C-terminal β-hairpin of NS2B, NS2Bc, was observed to be either disordered (open conformation) or bound to NS3pro complementing the substrate binding site (closed conformation). Enzymatically active constructs of flaviviral NS2B-NS3 proteases commonly used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…In agreement with previous studies , we also observed cleavage of linked WT ZIKV NS2B CF ‐NS3 pro . We therefore set out to identify the cleavage site, whether cleavage occurs in cis , that is, an individual protease cleaves its own linker or in trans , that is, a protease linker is cleaved by another ZIKV NS2B CF ‐NS3 pro protease in the sample and to compare the melting behaviors of cleaved and uncleaved protease constructs.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies , we also observed cleavage of linked WT ZIKV NS2B CF ‐NS3 pro . We therefore set out to identify the cleavage site, whether cleavage occurs in cis , that is, an individual protease cleaves its own linker or in trans , that is, a protease linker is cleaved by another ZIKV NS2B CF ‐NS3 pro protease in the sample and to compare the melting behaviors of cleaved and uncleaved protease constructs.…”
Section: Resultssupporting
confidence: 93%
“…The sizes of the autocatalytic cleavage products led us and others to conclude that there are two possible cleavage sites in ZIKV NS2B CF ‐NS3 pro , one at the NS2B CF C‐terminal R95 NS2B and one at R29 NS3 in the NS3 pro domain. The double mutation simultaneously removing both arginine residues successfully abrogated autocatalytic cleavage . Here, we mutated these sites individually and thus identified the relevant autocatalytic cleavage site to be at position R95 NS2B in the C‐terminus of the NS2B CF .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether the N2CN3N construct can monitor the NS2B conformational changes, we performed the SLC experiment with/without an active-site inhibitor, Nitrophenyl p-guanidinobenzoate (NPGB), which was known to induce conformational change of NS2B by NMR studies [36, 45]. As shown in Fig 2B , addition of NPGB (30 μM) significantly increased SLC (4.2-fold), compared to that of the DMSO control.…”
Section: Resultsmentioning
confidence: 99%
“…However, NMR studies also indicated that (1) the C-terminal portion of NS2B was still found to be flexible; (2) conformational changes were also observed and could be induced upon buffer manipulations; and (3) active-site inhibitor further stabilized the “closed” conformation [36, 6365]. In addition, recent NMR studies on the ZIKV NS2B-NS3 protease indicated that both closed and open conformations were observed even in the presence of different inhibitors [45, 66]. Overall these data indicated that although it is not clear what exact conformation of NS2B exists in vivo , the NS2B C-terminal region is quite flexible and may display multiple conformations, even though the “closed” conformation could be the main species.…”
Section: Discussionmentioning
confidence: 99%
“…S1). A recent NMR study has revealed that the open conformation also exists in gZiPro in solution . In the present study, we compared NMR spectra of bZiPro and gZiPro.…”
mentioning
confidence: 91%